AI in Placement Firms: Rekrute Morocco Case Study - Imane Louali; Manal EL Abboubi (Journal of Management and Science, 2026)
The introduction of artificial intelligence (AI) in organizations is generating growing interest, particularly in the field of recruitment, where its use raises numerous considerations. With this in mind, we conducted a case study within Rekrute, a pioneering placement firm in Morocco in AI development, to explore how this technology is deployed across different recruitment phases. Through a qualitative approach, our research examines how AI tools are integrated, the benefits they offer, and the concerns and challenges recruiters face throughout the process. Our findings reveal that AI plays a crucial role in optimizing candidate identification and attraction while facilitating preselection through objective assessment. Furthermore, Rekrute implements AI-driven solutions to support candidates in their career paths, enhancing recruitment efficiency while fostering career development. However, challenges remain, including the risks of algorithmic bias and the need for human validation to ensure fairness. This study thus provides insights into the impact of AI on recruitment, prompting reflection on the balance between technological innovation and the humanization of processes. It also highlights the importance of control mechanisms to monitor automated decisions, ensuring the ethical and effective application of AI in recruitment.